GABAergic Alterations in Neocortex of Patients with Pharmacoresistant Temporal Lobe Epilepsy Can Explain the Comorbidity of Anxiety and Depression: The Potential Impact of Clinical Factors - Rocha, Luisa; Alonso-Vanegas, Mario; Martínez-Juárez, Iris E.; Orozco-Suárez, Sandra; Escalante-Santiago, David; Feria-Romero, Iris Angélica; Zavala-Tecuapetla, Cecilia; Cisneros-Franco, José Miguel; Buentello-García, Ricardo Masao; Cienfuegos, Jesús (Frontiers in Cellular Neuroscience, 2015)
Temporal lobe epilepsy (TLE) is a chronic neurodegenerative disease with a high prevalence of psychiatric disorders. Temporal neocortex contributes to either seizure propagation or generation in TLE, a situation that has been associated with alterations of the γ-amino-butyric acid (GABA) system. On the other hand, an impaired neurotransmission mediated by GABA in temporal neocortex has also been involved with the pathophysiology of psychiatric disorders. In spite of these situations, the role of the necortical GABA system in the comorbidity of TLE and mood disorders has not been investigated. The present study was designed to identify alterations in the GABA system such as binding to GABAA and GABAB receptors and benzodiazepine site, the tissue content of GABA and the expression of the mRNA encoding the α1–6, β1–3, and γ GABAA subunits, in the temporal neocortex of surgically treated patients with TLE with and without anxiety, and/or depression. Neocortex of patients with TLE and comorbid anxiety and/or depression showed increased expression of the mRNA encoding the γ2-subunit, reduced GABAB-induced G-protein activation in spite of elevated GABAB binding, and lower tissue content of GABA when compared to autopsy controls. Some of these changes significantly correlated with seizure frequency and duration of epilepsy. The results obtained suggest a dysfunction of the GABAergic neurotransmission in temporal neocortex of patients with TLE and comorbid anxiety and/or depression that could be also influenced by clinical factors such as seizure frequency and duration of illness.